Experimental investigation on reduction of NOx emission of compression ignition engine fuelled with bio-diesel and diethyl ether. (2017) - Patel, Paresh D.; Chourasia, Sajan; Shah, Niraj K.; Lakdawala, Absar M.; Patel, Rajesh N.
The present work emphasis on the reduction of diesel engine emission using Jatropha-based bio-diesel and diethyl ether (DEE). The experiments show that with 20% (B20) addition of bio-diesel, the BSFC and BSEC increase by 7% and 10% while efficiency and emissions - CO, CO2, NOx, and HC - decreases by 1%, 64%, 5%, 18% and 48% respectively. However, it also shows that, even optimised blend (B20) is not able to meet stringent emission norms - particularly for NOx - set by EURO IV. For the further reduction of the NOx, DEE is added from 0% to 5% in B20. The results show that addition of 4% DEE, does not significantly influenced the engine performance, however reduction in NOx found to be 40% compared with diesel fuel. A hypothesis is proposed that, "The reduction in engine emission is due to improvement in combustion in presence of DEE". The hypothesis is validated through combustion analysis showing increase in peak pressure (Pmax ) by 7% and reduction in delay period by 1.5 degree with addition of 4% DEE in B20.